2014
DOI: 10.1590/s1984-82502014000200013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of Escherichia coli isolated from pasteurized milk in State of Paraná, Brazil

Abstract: Food contamination caused by enteric pathogens is a major cause of diarrheal disease worldwide, resulting in high morbidity and mortality and significant economic losses. Bacteria are important agents of foodborne diseases, particularly diarrheagenic Escherichia coli. The present study assessed the genetic diversity and antimicrobial resistance of E. coli isolates from pasteurized milk processed in 21 dairies in northwestern State of Parana, Brazil. The 95 E. coli isolates were subjected to antimicrobial susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These ndings corroborated with other studies [65,66,67]. Some other studies that used ERIC-PCR in E. coli isolated from other sources include Zhang et al [68] who reported genetic diversity analysis of E. coli serotypes isolated from retail foods in China and Oltramar et al [69] who reported genetic heterogeneity of E. coli isolated from pasteurized milk in Brazil. In our present study, river water samples were also collected and this is corroborated by a study by Lyautey et al [70] who reported distribution and diversity of E. coli in river water samples collected in Canada.…”
Section: Discussionsupporting
confidence: 86%
“…These ndings corroborated with other studies [65,66,67]. Some other studies that used ERIC-PCR in E. coli isolated from other sources include Zhang et al [68] who reported genetic diversity analysis of E. coli serotypes isolated from retail foods in China and Oltramar et al [69] who reported genetic heterogeneity of E. coli isolated from pasteurized milk in Brazil. In our present study, river water samples were also collected and this is corroborated by a study by Lyautey et al [70] who reported distribution and diversity of E. coli in river water samples collected in Canada.…”
Section: Discussionsupporting
confidence: 86%
“…ERIC-PCR has been reported as an effective tool in typing E. coli isolates from various sources including animals (Wan et al 2011) and water (Casarez et al 2007). Oltramari et al (2014) genotyped 95 E. coli isolates from milk and reported high genetic diversity among the isolates. They further reported common clustering of isolates from four milk samples processed in four different dairies, suggesting a single clone contaminant per milk sample and hence a common source of contamination.…”
Section: Phenotypic and Pcr Based Detection Of Antimicrobial Resistance And Putative Virulence Genesmentioning
confidence: 99%
“…Our results also indicated that the method is applicable to high throughput analysis. High genetic diversity also presented by ERIC-PCR results for E. coli in dairies products [ 8 ]. Both the ERIC and REP-PCR were shown high discriminatory index in Salmonella enteritidis research by Fardsanei et al [ 9 ].…”
Section: Introductionmentioning
confidence: 99%